PERAN TEKNOLOGI PENDIDIKAN DALAM PENGEMBANGAN KURIKULUM BERBASIS KOMPETENSI PADA KURIKULUM MERDEKA - Suci Mega Dian Sari; Mulyasaroh; Sholeh Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This literature review article aims to describe the role of educational technology in the development of competency-based curricula within the Indonesian “Kurikulum Merdeka” framework. The review synthesizes national and international studies on digital technology integration, teacher competency, and competency-based curriculum design, focusing on planning, implementation, and assessment processes. The findings indicate that educational technology supports data-based curriculum planning, student-centered and differentiated learning, as well as authentic and continuous assessment of competencies; however, challenges remain in terms of teachers’ digital skills, infrastructure gaps, and uneven access among schools. The article concludes that well-managed educational technology can become a key driver for realizing the goals of Kurikulum Merdeka to produce competent, character-based, and digitally literate graduates.